Factors Affecting Perceived Job Performance among Staff: A Case Study of Ban Karuna Juvenile Vocational Training Centre for Boys - Saetang, Jarunee; Sulumnad, Kodchakorn; Thampitak, Piyarat; Sungkaew, Thoungtong (The Journal of Behavioral Science, 2012)
The main objectives of this research were (1) to determine the relationshipsamong organizational factors (goal setting, and role ambiguity), personal factor(job satisfaction), and perceived job performance, and (2) to determine thepredictive power of organizational factors (goal setting, and role ambiguity), andpersonal factor (job satisfaction) on perceived job performance. A correlationalresearch design was used. 5 key informants were purposively selected from staffof Ban Karuna (a juvenile vocational training centre for boys in Bangkok) forexploring job performance problems. Information was collected from 95 staff ofBan Karuna. The research instruments consisted of questions for measuringinformation of (1) a demographic, (2) a goal setting, (3) a role ambiguity, (4) ajob satisfaction, and (5) a perceived job performance. Data analysis andhypothesis testing were performed by using Pearson’s product momentcorrelation and multiple regression. The multiple regression model with all threevariables could account for 43% of the variance in perceived job performance.However, only Role ambiguity had significant negative effect on Perceived jobperformance. Keywords: perceived job performance, goal setting, role ambiguity, job satisfaction